Pengaruh Kecepatan Pengadukan Dan Ukuran Partikel Adsorben Tanah Gambut Dalam Penyisihan Zat Organik, Besi (Fe) Dan pH Pada Air Gambut - Fitri, Rizki Febriani; HS, Edward; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Riau is a source of water for peaty areas or generally shallow swamp areas with brown water, high levels of humic acid, organic matter and iron. This study aims to determine the effect of stirring speed and particle size of peat soil adsorbent on the efficiency of removing organic substances, metals (Fe) and pH in peat water. The experiment was carried out by adsorption with a contact time of 2 hours by varying the particle size, namely 60, 80 and 100 mesh, stirring speed of 100, 150 and 200 rpm. While the fixed variables are 10% phosphoric acid activator, 300°C temperature and 10 gram mass. The concentration of organic matter removal was 57.2 mg/L with a percentage of 80.92%, metal (Fe) removal of 0.533 mg/L with a percentage of 86.57% at a particle size of 100 mesh and a stirring speed of 200 rpm while the pH was 7 with a particle size of 100 mesh and a stirring speed of 100 rpm. The adsorption capacity of peat water on organic matter was 24,27 mg/gr and iron (Fe) was 0,343 mg/gr at a particle size of 100 mesh and agitation speed of 200 rpm for 2 hours Keywords : Peat Water, Peat Soil, Adsorption, Removal Efficiency, Adsorption Capacity